Using Biotechnology to Make Biofuels from Algae as Renewable Energy - Rismen Sinambela; Ilham Samanlangi (CV. Get Press Indonesia, 2024)
According to research published in the Journal of Applied Phycology, algae have the ability to produce biofuels with five times higher energy efficiency compared to soybean plants, making it a highly efficient and sustainable option for renewable fuels. The goal of this research is to use biotechnology to create biofuels from algae as a renewable energy. This study used a laboratory experimental design with a quantitative approach. Population: Microalgae or green algae that have high potential in lipid production, such as Chlorella vulgaris or Spirulina platensis, which are commonly used in biofuel research. Sample: Several species of algae were selected to test their effectiveness as biofuels, including genetically engineered species and natural species as a comparison. The results of the ANOVA analysis showed significant differences in lipid levels between treatment groups. The results of the T/Post-hoc test confirmed that the genetically engineered species had higher lipid levels, supporting the efficiency of biofuels. The regression results showed a strong positive correlation (R² = 0.68), which supports other studies that found that microalgae can produce biomass in a relatively short time with a controlled environment, making it efficient for large-scale biofuel production. The conversion efficiency of lipids to biofuels reached 85.5%, indicating that the transesterification method used in this study is very effective in converting algae lipids to biodiesel. The use of biotechnology in the production of biofuels from algae has great potential as an efficient and sustainable renewable energy source.